Job satisfaction and mental wellbeing among high school teachers in Malaysia - Leow, Kenneth; Lee, Cheng Ean Catherine *; Leow, Serena Wai Yee * (Malaysian Psychological Association, UKM, 2020)
Job satisfaction plays an important role in regard to teachers’ continuation in the teaching profession. School-based factors such as relations with colleagues, parents, and student behavior are important factors that contribute to teachers’ fulfillment in their workplace. This study examined the relationship between job satisfaction and wellbeing among high school teachers in Malaysia. A total of 111 full-time high school teachers (99 females, 12 males) from two schools located in Kuala Lumpur, Malaysia, completed measures of the Teacher Job Satisfaction Scale and Short Warwick-Edinburgh Mental Wellbeing Scale. Data were analyzed using correlation coefficient and regression analysis. The results indicated significant positive correlation between teachers’ job satisfaction and wellbeing. More specifically, teachers’ satisfaction with students’ behavior and students’ parents were significant predictors of mental wellbeing. This study highlighted job satisfaction that teachers themselves may have for positive personal relationship with co-workers, students, and student’s parents, providing further understanding of the contribution of job satisfaction to teachers’ mental wellbeing. This study helps complement previous studies by providing a further understanding on the contribution of job satisfaction to teachers’ wellbeing in the Malaysian context.